Airway Management in Surgical Patients With Obstructive Sleep Apnea. (14th April 2021) - Seet, Edwin; Nagappa, Mahesh; Wong, David T.
Abstract : Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder, and the difficult airway is perhaps the anesthesiologists' quintessential concern. OSA and the difficult airway share certain similar anatomical, morphological, and physiological features. Individual studies and systematic reviews of retrospective, case-control, and large database studies have shown a likely association between patients with OSA and the difficult airway; OSA patients have a 3- to 4-fold higher risk of difficult intubation, difficult mask ventilation, or a combination of both. The presence of OSA should initiate proactive perioperative management in anticipation of a difficult airway. Prudent intraoperative management comprises the use of regional anesthesia where possible and considering an awake intubation technique where there is the presence of notable difficult airway predictors and risk of rapid desaturation following induction of general anesthesia. Familiarity with difficult airway algorithms, cautious extubation, and appropriate postoperative monitoring of patients with OSA are necessary to mitigate perioperative risks.